2020
DOI: 10.1155/2020/7302141
|View full text |Cite
|
Sign up to set email alerts
|

Improved Nonlinear Nishihara Shear Creep Model with Variable Parameters for Rock‐Like Materials

Abstract: Creep property is an important mechanical property of rocks. Given the complexity of rock masses, mechanical parameters change with time in the creep process. In this work, a nonlinear function for describing the time-dependent change of parameters was introduced and an improved variable-parameter nonlinear Nishihara shear creep model of rocks was established. By creating rock-like materials, the mechanical properties of rocks under the shear creep test condition were studied, and the deformation characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…erefore, the free section of the prestressed anchor cable is a weak link that is susceptible to shear failure. Lin et al studied the anchorage stress and deformation of the anchorage joint under shear action through direct shear test and found that the inclination angle of the bolt has an effect on the shear strength of the joint plane and improved the shear creep model of rock-like materials [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the free section of the prestressed anchor cable is a weak link that is susceptible to shear failure. Lin et al studied the anchorage stress and deformation of the anchorage joint under shear action through direct shear test and found that the inclination angle of the bolt has an effect on the shear strength of the joint plane and improved the shear creep model of rock-like materials [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the mining industry [1][2][3], tailings as the waste after ore smelting also increased sharply [4][5][6]. The primary disposal method of tailings is to deposit them on the surface of the earth to form tailings dams [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ebrahimi et al investigated static stability and free vibration characteristics of functionally graded (FG) nanobeams [20] and so on [21][22][23][24]. What is more, a suitable computational modeling and theoretical analysis could also help to solve practical engineering problems [25][26][27][28][29], especially in the underground engineering [30][31][32][33], which had experienced excellent performances. So, all the above results inspired us to establish a suitable mechanical model and mathematical modeling to get a new way to analyze the vertical instability of shaft lining structures.…”
Section: Introductionmentioning
confidence: 99%